Analysis of the Effectiveness of Fluidized Bed Dryer in Black Tea Processing Using the OEE Approach - Prayitno, Hadi; Firmando, Moses; Panuju, Achmad Yahya Teguh; Lestari, Rahayu; Rachmawati, Tety (Politeknik Caltex Riau, 2025)
This study evaluated the operational effectiveness of the Fluidized Bed Dryer (FBD) machine in the traditional black tea drying process using the Overall Equipment Effectiveness (OEE) framework, which includes availability, performance efficiency, and quality rate, as defined in ISO 22400-2:2014. Data collected from January to June 2023 indicated an average OEE of 83.66%. Although availability was consistently high (94–100%) and product quality maintained at 100% throughout the month, performance efficiency varied considerably, dropping to 69% in January and 66% in April, primarily due to operational delays and unstable machine utilization. These results indicate that performance efficiency was the main factor affecting OEE and total productivity. It recommends implementing condition-based maintenance procedures and real-time process monitoring systems to minimize unexpected downtime and enhance operational stability. Better regulation of input load, airflow, and drying temperature was crucial to ensure consistent performance and support product standardization in accordance with SNI 2891:2016, ultimately enhancing the competitiveness of the black tea processing industry.